PENGARUH KOMUNIKASI, DISIPLIN KERJA DAN KEPIMPINAN TERHADAP KINERJA KARYAWAN DI PT. DAYA KOBELCO CMI PEKANBARU - Mhd. Febrizon '; Nuryanti '; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. CMI Kobelco Pekanbaru power in order to determine the effect of variable communication, Work Discipline and Leadership simultaneously on Employee Performance in PT. Kobelco power CMI Pekanbaru. This study uses primary data obtained from interviews and giving questionnaires to all employees of PT. Kobelco power CMI Pekanbaru. Secondary data were obtained relating to the object and the organizational structure of the population in this study were all employees that numbered 61 people and sampled. The analytical method used in this research is multiple linear regression method. From the testing that has been done, simultaneous regression test (Test-F) indicates that the variable Communications, Work Discipline and Leadership simultaneously significant effect on employee performance. From the results of the partial test (t-test) showed that the variables of Communication, Work Discipline and Leadership significant effect on employee performance. The result of the calculation of the coefficient of determination (R2) is equal to 0.796, which means, variable Communication, Work Discipline and Leadership jointly influence on employee performance, while the rest influenced by other variables not examined in this study.Keywords : Communication, Work Discipline, Leadership and Employee Performance